In vitro germination of Calibrachoa thymifolia and Calibrachoa missionica native to Argentina - Tombion, Leticia (2023)
Calibrachoa is a genus native to South America wich belongs to the Solanaceae family. The use of seeds of calibrachoa species native to Argentina serves as a source of natural variability and for research purposes, so their in vitro germination represents a fast and reliable tool compared to other traditional germination techniques. Therefore, in this work the in vitro germination of C. thymifolia and C. missionica was evaluated under Murashige and Skoog and Woody plant medium, and it was found that both are efficient for the germination of these species. In turn, it was determined that, under these conditions, C. thymifolia germinates more seeds in a shorter time than C. missionica.